Yahoo Web Search

  1. Sort by

  1. No. GTA V needs both a decent CPU and graphics https://dev1... is about the minimum https://www.youtube.com/watch?v=JojKyWpNW2I You find many videos showing...

    2 Answers · Computers & Internet · 09/11/2018

  2. u = 8i + 7j → tan(u) = 7/8 v = 7i - j → tan(v) = - 1/7 tan(a - b) = sin(a - b) / cos(a - b) → recall...b)] / [1 + tan(a).tan(b)] → adapt this result to your case tan(u - v) = [tan(u) - tan(v)] / [1 + tan(u).tan(v)] tan(u - v) = [(7/8) - (- 1/7...

    2 Answers · Science & Mathematics · 29/04/2019

  3. ..., this is a little messy. a) position s(t) = ∫ v(t) dt s(t) = ∫ [2sin(t) i + 2cos(t) j + t k] dt = -2cos(t) i...k ◄ c) unit tangent T(t) = s'(t) / ||s'(t)|| = v(t) / ||v(t)|| ||v|| = √[(2sin(t))² i + (2cos(t))²...

    1 Answers · Science & Mathematics · 29/06/2019

  4. v = ⟨a, b, c⟩ for example yields vv = a² + b² + c² = (√(a² + b² + c²))² = ||v||²

    3 Answers · Science & Mathematics · 04/08/2019

  5. V = kq/r so r = kq/V = 8.98755179e9 * 1e-5/1e4 = 8.98755179e9 * 1e-5/1e4 = = 8.98755179e9...

    3 Answers · Science & Mathematics · 15/09/2019

  6. Integrate from t = 0 to t = 1 u = t^2 du = 2t * dt dv = e^(-3t) * dt v = (-1/3) * e^(-3t) (-1/3) * t^2 * e^(-3t) - (-2/3) * int(t * e^(-3t) * dt) => (-1/3...

    3 Answers · Science & Mathematics · 21/02/2019

  7. Integrate the equation to get displacement v(t) = 5t - t^2 s(t) = 1/2 * 5t^2 - 1/3 * t^3 + c and s(0) = 3 therefore c = 3 when...the negative displacement found above. So you need to find the time at which v = 0. ie the time at which the body changes direction v(t) = 0 t(5-t) = 0 so...

    1 Answers · Science & Mathematics · 22/11/2018

  8. v = sin(pi * t) s = (-1/pi) * cos(pi * t) + C s = 0 when t = -3 0 = (-1/pi) * cos(-3pi) + C 0 = (-1/pi) * (-1) + C 0 = 1/pi + C -1/pi = C s = (-1/pi) * cos(pi * t) - 1/pi s = (-1/pi) * (cos(pi * t) + 1)

    1 Answers · Science & Mathematics · 18/07/2019

  9. IIRC, Godfrey v Georgia was mostly about the wording of the law in Georgia...

    1 Answers · Arts & Humanities · 12/05/2019

  10. 8u - 8 = 4 - 4w 8u + 4w = 12 2u + w = 3 w = 3 - 2u w = u + v 3 - 2u = u + v v = 3 - 3u 8u = 4 + 6v 8u = 4 + 6 * (3 - 3u) 4u = 2 + 3 * (3 - 3u) 4u = 2 + 9 - 9u 13u = 11 u = 11/13 v = 3 - 3u v = 3 - 33/13 v = 39/13 - 33/13 v = 6/13 w = u + v w = 11/13 + 6/13 w = 17/13

    2 Answers · Science & Mathematics · 16/09/2019

  1. Try asking your question on Yahoo Answers